(3QSGdI aj Ydhe GdMbGFb hMce GdObGFbs - (3GdTjN GdcGeds
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GdehLhOGJ Ydi hLhOg OdjdkG hHYO agPg GdQSGdI GdTQjaI ai Ydhe GdMbGFb hMce GdObGFb hai cd aUd CUhd GdChd ai MbjbI GdMbGFb s
(3BNQgG (B:s
(3hfSHI GdMb GdPi hMOJg PGJjI cfjJg GdhGMO Edi LejY GdGYOGO dG jJMbb cd YOO GdG HGdhGMO hEPG aQV GdG jQJaY hGMO ai GdGYOGO Je s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI (B27s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3jdjg ahGFO hfbhds
(3eUOQ GbJfGA GdCUd (B:s
(3ShQjG (B(9237) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs